# DIIFERENTIAL EQUATION: $(x^2 + y^2) dx + x (3x^2 - 5y^2) dy = 0$

Submitted by Sydney Sales on July 16, 2016 - 4:45pm

( x^2 + y^2 ) dx + x (3x^2 - 5y^2 ) dy = 0

- Log in to post comments
- 2476 reads

Submitted by Sydney Sales on July 16, 2016 - 4:45pm

( x^2 + y^2 ) dx + x (3x^2 - 5y^2 ) dy = 0

- Log in to post comments
- 2476 reads

## $(x^2 + y^2)\,dx + x(3x^2 -

$(x^2 + y^2)\,dx + x(3x^2 - 5y^2)\,dy = 0$

The variables are not separable

The equation is not homogeneous

Try:

$\dfrac{dx}{dy} + \dfrac{x(3x^2 - 5y^2)}{x^2 + y^2} = 0$

The equation is not linear.

Try:

$N = 3x^3 - 5xy^2$ → $\dfrac{\partial N}{\partial x} = 9x^2 - 5y^2$

The equation is not exact

Try:

$\dfrac{\dfrac{\partial M}{\partial y} - \dfrac{\partial N}{\partial x}}{N} = \dfrac{2y - 9x^2 + 5y^2}{3x^3 - 5xy^2}$

The equation does not have an integrating factor that is a function of x alone

Try:

$\dfrac{\dfrac{\partial M}{\partial y} - \dfrac{\partial N}{\partial x}}{N} = \dfrac{2y - 9x^2 + 5y^2}{x^2 + y^2}$

The equation does not have an integrating factor that is a function of y alone

Wala pa akong nakitang solution. Kung meron ka na, pease share.

## eto po yung answer:

eto po yung answer:

2y^5 - 2x^2 ( y^3) + 3x = 0

## Are you sure your equation is

Are you sure your equation is correct? And based on your answer key, there should be an initial condition because there is no constant c in your answer.

## The equation is wrong it

The equation is wrong it should be y(x^2+y^2)dx+x(3x^2-5y^2)dy=0, when x=2 , y=1